Pengaruh Lifestyle, Perceived Quality dan Atribut Produk Terhadap Keputusan Pembelian Kain Besurek pada Atik Batik di Kota Bengkulu - Dimas Dimas; Markoni Markoni; , Veny Puspita (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The aim of this research is to find out how much influence lifestyle, perceived quality and product attributes have on the decision to purchase Besurek Cloth for Batik Atik in Bengkulu City. The research is quantitative research. The data source in the research comes from distributing questionnaires (Google Form) which will be distributed online via WhatsApp and Instagram to respondents who have purchased Besurek batik cloth at Bengkulu city batik shops. The population in this study were all customers of Besurek Cloth at Atik Batik in Bengkulu City. The sample uses the Hair formula where the number of indicators (28) x5 = 140 respondents of customers of Besurek Cloth on Atik Batik in Bengkulu City with a purposive sampling method. The analysis tool used in this research uses SPPS 22. The research results show; (1) Lifestyle has a partial and positive influence on the decision to purchase Besurek cloth for Batik Atik in Bengkulu City. (2) Perceived Quality has a partial and positive influence on the decision to purchase Besurek cloth for Atik Batik in Bengkulu City. (3) Product attributes have a partial and positive influence on the decision to purchase Besurek cloth for Atik Batik in Bengkulu City. And (4) Lifestyle, perceived quality, and product attributes on purchasing decisions for Besurek Cloth at Atik Batik in Bengkulu City have a simultaneous influence.